Independent MPPT and voltage regulation of dual input DC - DC converter with a voltage multiplier cell. Issue 1 (31st December 2023) - Appikonda, Mohan; Kaliaperumal, Dhanalakshmi
ABSTRACT: A dual input boost DC–DC converter (DIBC) with combined voltage multiplier cell, the larger duty ratio (greater than 0.5), and the overlapping switching signal are required to obtain high voltage gain. This paper investigates the independent maximum power point tracking (MPPT) implementation on two solar photovoltaic (PV) energy sources along with the output voltage regulation of the DIBC during load and input voltage disturbances. For maximal power extraction, a single ended primary-inductance converter (SEPIC) is designed at each input, one with the perturb and observe (P and O) approach and the other with the incremental conductance algorithm. The small-signal transfer function model is used to design the voltage regulator. The MPPT algorithms for maximum power extraction as well as the inner current-loop and outer voltage-loop control approach have been implemented simultaneously. Duty ratio of the DIBC MOSFETs as a function of the converter output voltage and duty ratio of the SEPIC MOSFET as a function of MPPT are used to generate the switching signals. An experimental two 100W PV sources are developed using real-time solar simulator with the 200 W DIBC and controller is designed using XILINX SPARTAN-6 FPGA board. MATLAB simulation and experimental results ensure the active current sharing among the sources, reference output voltage (156.6 V) tracking, voltage regulation (below 5%) under different scenarios, and independent MPPT simultaneously.